Representações de professores dos anos iniciais do ensino fundamental sobre o currículo e o ensino de ciências no município de Cascavel. - Scheifele, Alexandre (2013)
The origins of the discussions about Brazil‘s school curriculum go back to the 30ies, with publications which focused on the theme, shaping the curriculum according to educational theories broadcasted at the time. Since then, countless researches focus on the theme, which go through different aspects as those social, political, economic, cultural, among others, and demonstrate the preoccupation of educators with the curricular policies and with the ideologies that permeate them. Given this situation, this paper seeks to give continuity to this legacy of investigations in regards to curriculum, and it concentrates itself on the Curriculum for Cascavel‘s Municipal Public Teaching Network, more specifically in the discipline of Sciences. This curriculum, relatively new, with implementation and use since 2008, guides teaching in a school network composed of 61 municipal schools, and has as its theoretical premises the Historical-Critical Pedagogy, the Dialectical and Historical Materialistic Method and the Historical-Cultural Psychology. With the objective of researching how this curriculum had been constructed, under the conception of nine teachers that participated directly in this construction and, in counterpart to that, eleven teachers who did not directly participate in this construction, but who use this curriculum nowadays to plan their classes, we have chosen the semi-structured interview with the usage of guide-questions and an audio-recorder, in order to later transcribe those interviews. To analyze these transcriptions, we have guided ourselves on the Theory of Social Representations, which allowed us to identify the representations of the teachers about the construction and applicability of this curriculum. It was possible to identify, then, in the representations of the teachers, a central core which was called as ―Guidance‖, as well as its peripheral systems and, from that, we were able to acknowledge some of our hypothesis. We were able to list important information about the process of construction of this curriculum, even if only in intention, it was to be a collective construction, in which the teachers tried hard to write the premises which fundament the curriculum and, later, its implementation, and went through a process of formation for its usage. This formation showed positive points, in regards to the broadening of knowledge of the teachers about the theoretical validity of Cascavel‘s Curriculum, as well as negative points, when we discuss the jargons and misconceptions transmitted in such courses. It was possible to perceive that the teaching of Sciences hardly went forward in regards to the improvements predicted by the curriculum and that the teachers find it necessary to have a restructuring this curriculum, mainly in its contents, which are given in excessiveness of this curriculum, mainly in its contents, which are given in excessiveness.